Gender differences in the causal relation between adolescents' maths self-concept and scholastic performance - Cristina Antunes (2007)
Mathematics is a core subject in every school curriculum and it is strongly correlated with maths self-concept, which is defined as the subjective feelings and beliefs about one's competence in maths. In general, boys tend to report higher maths self-concept than girls, but the difference between boys and girls' maths scholastic performance is low or even inexistent. Some authors maintain that academic self-concept can play an important role as a motivational variable, promoting self-confidence and investment in the learning process. This study examined the causal relations between maths self-concept and maths scholastic performance in four cohorts of boys and girls within a three-wave longitudinal study. The first two cohorts were composed of 187 girls and 139 boys attending grades 7 and 8 at Time I and the third and fourth cohorts were composed of 167 girls and 123 boys attending grades 9 and 10 at Time 1. Structural Equation Modelling was used to test the fit of several models of causal relations. The results revealed that for the first two cohorts the best models were reciprocal and skill-development for both boys and girls. However, for the older students, a reciprocal model gave a best fit for the boys, but for the girls there was only one significant effect from maths self-concept to maths scholastic performance. Results are discussed on the basis of gender-related differential learning expectancies.